Visceral leishmaniasis in kidney transplant recipients and candidates: an integrative review of the last 20 years - Osvaldo Mariano Viana Neto; Ednaldo Pereira Lima Sobrinho; Beatriz Fontenele Felix; Gustavo Ferreira da Silva; Pedro Yago Lima de Mesquita; Francisco Mikael Alves Mota; Evelyne Santana Girão; Maria Alice Sperto Ferreira Baptista; Celia Sebastiana de Jesus Fazzio; Elizabeth De Francesco Daher; Wanessa Trindade Clemente (Brazilian Journal of Nephrology)
Abstract Introduction: Leishmaniasis is a potential concern for solid organ transplant (SOT) recipients, particularly those from endemic regions. Among SOT procedures, kidney transplantation (KT) is the most common. This study aims to synthesize the evidence about visceral leishmaniasis (VL) in KT candidates and recipients, with a focus on risk factors and associated outcomes. Methods: This integrative review analyzed studies from the past 20 years, focusing on disease profile, treatment, prognosis, and risk of asymptomatic infection. Results: A total of 32 articles were included. Of the KT recipients, 85.7% were male, with an average age of 42.5 years. The average timespan since symptom onset was 54.7 months. Renal function impairment was reported in 64% of patients, with an associated mortality rate of 15%. Post-treatment relapse occurred in 10–37.5% of patients. Among KT candidates, 13.9% were seropositive for Leishmania spp. Conclusion: VL is an infrequent condition among KT recipients, limiting the quality of the available evidence. Early detection and prompt treatment are crucial for improving outcomes. While renal function impairment is common, it rarely leads to graft rejection. In the reviewed studies, the coexistence of VL and cutaneous or mucocutaneous forms was linked to higher mortality. Recurrences are common and require individualized management strategies. Hemotransfusion poses a potential infection risk, although routine screening in blood banks is not yet recommended.